Odpowiedź:
5) 3,2y – 4 = 6,7y - 4 3,2y -6,7y = -4-4 - 3,5y = - 8 razy -1 3,5 y= 8 y=8/ 3,5 y = 2,28
6) 1 - 2(0,2x - 3) = 0,4(3 + x) + 5 1 - 1,8x +6 = 1,2 + 0,4x +5
-1,8x -0,4x =6,2-7 - 2,2x = - 0,8 / razy - 1 x= 0,8 : 2,2 x = 0,36
7)-(4 + x) = 2(3 - x) -4 -x = 6 - 2x -4 - x +2x = 2 + 4 x= 6
8) (x - 7) - 2(3x + 5) = 3 x -7 -6x -10 = 3 - 5x = 3 +17 - x= 20 /5 x= -4
9) (367 + 6)-y=( 269 + 9) 376 - y = 278 -y = 278 - 376 / razy -1
y= -278 +376 = 98
10) 2y - (3y + 1) = 6 2y - 3y +1 =6 - y = 6 -1 /razy -1 y = -5